Self-disclosure and stages of relationship formationin social networking sites the case of facebook - Arista, Mark Joshua Oblan; Ricopuerto, Maicah Bautista (2012.)
This study contributes to literature on computer-mediated communication, particularly online relationship formation. It serves as a source of information for people to know what kind of information they should disclose online, specifically on Facebook, and helps users to analyze and identify differences between their online and offline relationships. This study analyzed how online relationships are formed in Facebook in terms of self-disclosure and how users form relationships through their Facebook accounts. A total of 420 respondents answered the survey questionnaires designed to analyze online self-disclosure among Facebook users and the stages of relational development in Facebook. Results showed that respondents were reluctant to disclose information regarding personal matters, beliefs or religious convictions, relationships, and sex; and were willing to disclose information regarding their interests. Furthermore, it was found that the probability of online relationships like romantic relationships to develop is relatively small while relationships like being friends or acquaintances have the bigger chance to build up. It was also found that if a relationship was developed online, it undergoes certain stages which are similar to the stages of face to face relationships. This study concludes that Facebook users do not consider the site as a proper or right medium/channel for self-disclosure, especially of highly private and personal matters, which is the ground for the relationships to develop. Meaning, the development of online romantic relationships is not always possible. Basically, interpersonal relationships in Facebook are confined to acquaintanceship which is grounded on common interests. Future researchers could also explore other aspects of online relationships like anonymity or look at the role of Facebook in maintaining already existing relationship. An unstructured interview which can gather valuable insights from the respondents is also recommended. Other researchers can also test the quality and longevity of relationships which are initiated in Facebook and brought face-to-face.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Social Networking; Facebook